MOLECULAR GENETIC ANALYSIS OF COX2 GENE POLYMORPHISM IN CHRONIC POLYPOSIS RHINOSINUSITIS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Analysis of the contribution of the COX2 gene polymorphism to the frequency of occurrence, development and clinical course. The prevalence of the rs20417 76 G/C polymorphism in the COX2 gene was analyzed among patients with chronic polyposis rhinosinusitis and chronic rhinosinusitis and in the control group. We can conclude that there are no significant differences in the frequency of detection of allelic and genotypic variants of the 76 G/C polymorphic locus in the COX2 gene.